SEMANTIC DERIVATION OF THE VERB CONTENTS IN THE COGNITIVE ASPECT - Khudoyarova Gulnara Nuriddinovna (Galaxy International Interdisciplinary Research Journal, 2022)
The purpose of this study is to try to consider verbal semantics from the point of view of describing the processes of cognition and generation of speech carried out by the Speaker, i.e. in a cognitive aspect. This approach is relevant for solving applied problems of linguistics, in particular for the methodology of teaching Russian as a foreign language, since it allows to adequately model the process of teaching a foreign language. The novelty of this study lies in the fact that the cognitive process carried out by the Speaker is presented as derivational. Derivation at work is understood extremely broadly, as a process of transition from deep (non-linguistic) structures of representation knowledge to superficial (linguistic).